FEATURES OF CREATING AND USE THE NATURE TRIPS IN THE EDUCATIONAL ENVIRONMENT OF PRESCHOOL EDUCATIONAL INSTITUTIONS - Оshurkevych, Nataliia (Educological discourse, 2018)
The main conceptual foundations of the upbringing of preschool children are realized in institutions of preschool education of Ukraine. Favorable conditions for environmental education and development of preschool children are the creation of an ecological educational environment in the preschool institution. K. Krutyi (2016) and T. Ponimanska (2004) disclose the concept of "developmental environment" as a complex of special conditions that ensure the life of children of preschool age. However, the research of O. Kononko (2003, 2013) allows us to formulate the concept of a developmental environment in the educational space of the institution of preschool education as a system consisting of the interaction of four environments: the natural, substantive, social and personal space of the "I" child. The work of N. Goropaha (2014) and Z. Plokhii (2013) are devoted to studying the features of environmental education in pre-school educational institutions. The authors investigate the problems of creating an ecological development environment in preschool institutions and conditions of emotional and aesthetic perception of nature, development of intellectual and humanistic-oriented feelings in relation to nature. A generalized analysis of scientific and pedagogical periodicals makes it possible to ascertain the interest of the pedagogical community in the problems of environmental education of the younger generation and the creation of an ecological environment in educational institutions. The definition of the concept "ecological path" as an element of the ecological development environment is presented and the relevance of the use of the ecological path in the educational environment of the institution of preschool education is substantiated. The types of ecological tracks, the purpose of their creation and the functions performed are determined. The project of the ecological pathway on the territory of the institution of preschool education has been developed, three stages of work on creation of the ecological trail have been determined and the passport of the ecological trail has been issued.